Defining Learning Outcomes as a Prerequisite of Implementing a Longitudinal and Transdisciplinary Curriculum with Regard to Digital Competencies at Hannover Medical School. (July 2021) - Foadi, Nilufar; Koop, Christian; Mikuteit, Marie; Paulmann, Volker; Steffens, Sandra; Behrends, Marianne
Background: Worldwide educational programs face the challenge how to define and integrate digital competencies in medical education. This article describes the implementation of learning outcomes with respect to digital competencies in the compulsory curriculum at Hannover Medical School (MHH). Methods: An interdisciplinary MHH project group was constituted consisting of physicians and experts in medical informatics and in curriculum development. Over the course of 7 work sessions the group compared different international and national frameworks dealing with digital competencies for physicians. By a consensus driven approach the working group drew up a collection of learning outcomes which were regarded relevant to be incorporated in the curriculum at MHH. Results: The analysis of different frameworks indicated that data literacy is a central domain within all viewed preexisting catalogs. During the course of the project group analysis, 57 learning outcomes with respect to digital competencies were identified as necessary to be integrated in the compulsory curriculum. They were divided in 5 main categories: "handling of medical data, " "the digital infrastructure of the health system, " "scope of application: usage in patient care and in the field of preventive medicine, " "medico-legal and ethical basics, " and "transformation processes in medicine due to digitalization." Conclusions: The MHH project group concluded that medical students should be taught digital competencies that enable an understanding of underlying functional principles of digital systems rather than their correct utilization. The presented project indicates that a close interdisciplinary collaboration of physicians and medical informaticians can be a promising approach to incorporate digital competencies in the undergraduate medical curriculum.